Preparación y caracterización físicoquímica de sistemas biomiméticos sobre superficies lisas y nanoestructuradas: estudio de sus interacciones con moléculas y nanopartículas - Maya Girón, Julie Viviana (2013)
Transport and interaction of nanoparticles (NPs) with biological membranes is a relevant aspect in its employment in the field of nanomedicine; in diagnosis of diseases and other applications of nanotechnology. The huge variety of designs of NPs in terms of shapes, sizes and surface modifiers opens numerous questions about how they modify membranes in terms of possible formation of pores, defects or phenomena of permeation of water or ionic species. In this presentation we report the synthesis and characterization of silver nanoparticles capped with 4- mercaptobenzoic acid which constitute adequate probes to study by Raman spectroscopy the interaction of NP with supported lipid bilayers as model system for membranes. As a first stage, we have studied the interaction of Ag NPs with alkanethiol monolayers self-assembled on gold